Identification of suppression mechanisms and antifungal compounds from Trichoderma virens against Ganoderma boninense - Lee, Angel Pei Lee (2016)
Ganoderma boninense has been identified as the pathogen that causes basal stem rot (BSR), a devastating disease affecting the oil palm tree. Trichoderma has long been recognized as a potential antagonistic biological control agent (BCA) against pathogenic fungi that are responsible for several plant diseases. The success of Trichoderma isolates as potent BCAs is due to the antagonistic characteristics such as mycoparasitism and antibiosis. Therefore, this study attempts to identify the mechanisms involved in the suppression of G. boninense and the antifungal compounds released by endophytic Trichoderma. Two potential endophytic Trichoderma isolates, namely Trichoderma virens 7b and Trichoderma virens 159c were assessed through in vitro assays. Trichoderma able to produce siderophore and able to chelate the iron under iron starvation. The culture filtrates of these Trichoderma isolates were then extracted using hexane, ethyl acetate (EtOAc) and butanol (BuOH), respectively. The resulting extracts were tested against G. boninense PER 71 for their antifungal activity through a modified well diffusion assay. The active fraction was further fractionated with chromatographic methods and the composition of the active fraction was analyzed with gas chromatography-mass spectrometry detector (GC/MSD). Both Trichoderma strains were highly active in producing siderophores according to the qualitative CAS reaction observation. Hexane extract of T. virens 7b and ethyl acetate extract of T. virens 159c were found to cause the highest inhibition against G. boninense PER 71 in inhibition radial growth (PIRG) (62.60% ±6.41 and 78.39% ±5.40, respectively). The activity of each extract was further demonstrated under the scanning electron microscope (SEM) where severe deformation of G. boninense PER 71 mycelia was observed at the inhibition region. The active fractions of T. virens 7b constituted of compounds such as ketones, alcohols, aldehydes, lactones, sesquiterpenes, monoterpenes, sulphides and free fatty acids whereas T. virens 159c produced ketones, aldehydes, acetamide,alcohol, lactones and free fatty acids. Secretion of phenylethyl alcohol was found to be produced by both T. virens isolates. The findings of this study contribute to the understanding of the potential mechanisms involved in the suppression of G. boninense by endophytic Trichoderma.